Dexamethasone sodium phosphate intercalated layered double hydroxides and their therapeutic efficacy in a murine asthma model. Issue 30 (4th March 2015) - Wang, Wen-Rui; Li, Ang; Mei, Wei; Zhu, Rong-Rong; Li, Kun; Sun, Xiao-Yu; Qian, Ye-Chang; Wang, Shi-Long
Abstract : Schematic diagram showing the intercalation of Dexa into the MgAl–LDH interlayers. Abstract : Although inhaled steroids are the first choice to control asthma, frequent corticosteroid administration is associated with many side effects such as adrenocortical suppression, Cushing's syndrome and osteoporosis. The purpose of this study was to develop a drug delivery system to overcome the limitation of corticosteroid administration and improve the therapeutic efficacy in an ovalbumin (OVA)-induced allergic asthma rat model. The intercalation of dexamethasone sodium phosphate (Dexa) into layered double hydroxides (LDHs) was achieved by the co-precipitation method and the obtained nanoparticles (Dexa–LDHs) have an average diameter of approximately 100 nm. The X-ray diffraction patterns and FT-IR spectra of the Dexa–LDHs indicated that the Dexa molecules were successfully intercalated into the LDHs via electrostatic interactions. 13 C NMR chemical shifts were analysed to clarify the characteristic changes in functional groups after intercalation. Elemental C/H/N and inductively coupled plasma (ICP) analysis revealed the compositions of the nanohybrids. The thermal stability of Dexa anions was enhanced by holding together within the LDHs layers. The drug loading was estimated to be 50.8% and a gradual and biphasic in vitro release behavior of the drugs from LDHs in pH = 7.4 phosphate buffered saline (PBS) was observed. The parabolic diffusion model was used to simulate the release kinetics of Dexa from the LDHs. The potential of Dexa–LDHs as an anti-asthmatic agent was evaluated in the allergic asthma rat model. The results showed that Dexa–LDHs were more effective than Dexa to reduce the number of inflammatory cells in bronchoalveolar lavage (BAL) fluid. Furthermore, Dexa–LDHs significantly inhibited the increase of T-helper-2-type cytokines such as IL-4 and IL-13, and more effectively suppressed airway hyperresponsiveness. In conclusion, these results suggest that Dexa–LDHs could enhance the anti-asthmatic effect of Dexa in the treatment of allergic asthma rats. Our work indicated that LDHs could be a promising candidate for the exploration of new Dexa formulations.